(untitled) (Journal of the College of Basic Education, 2024)
The aim of the research is to determine the effect of differentiated education strategies on the achievement and critical thinking skills of fourth-year mathematics students in Iraq. The research sample consisted of (60) students, who were randomly distributed into two experimental and control groups. The research tools included two tests that were built according to special standards. The first: the achievement test, which consisted of (40 items, all of the multiple-choice type. All items were presented to the arbitrators. In the specialty, it was accepted with a high rate of acceptance of the items, and the other was the critical thinking skills test consisting of (20) items, which was prepared according to critical thinking skills and was applied to a reconnaissance sample to determine the specific time and the level of ease, difficulty, and distinction, and it became ready for application; equivalence was conducted in some variables (Intelligence, chronological age, previous knowledge in mathematics, achievement in mathematics, critical thinking skills, and the statistical package (SpSS) (version 21) was used to conduct equivalence and homogeneity, find statistical differences, and the effect size equation. The results showed that the study was in favor of the experimental group. The researcher put forward proposals including Procedure Studying other stages and variables such as other creative thinking skills, the researcher recommended that schools pay attention to differentiated education. Training all teachers on the basics of critical thinking skills.